"The Miracle Worker": A holistic approach to language acquisition pedagogy - Retnowati, Nanik; Redjeki, Indah Sri; Septian, Kiasati Yusrina; Salimah, Najwatus (TLEMC (Teaching and Learning English in Multicultural Contexts), 2024)
This study investigates the pedagogical potential of The Miracle Worker (1962) as a teaching medium in Language Acquisition courses, with a dual focus on linguistic development and character education. Employing a qualitative descriptive method with film content analysis, the research systematically examines key scenes and character interactions to identify how theoretical principles of language acquisition—such as behaviorist, nativist, interactionist, and affective approaches—are reflected in Helen Keller’s learning journey. Data were collected through close scene analysis, thematic coding, and interpretation aligned with major theories of language development.  The findings reveal that the film presents a rich, multidimensional representation of the language acquisition process, highlighting the importance of tactile-based instruction, emotional support, and socially mediated interaction. Helen Keller’s journey illustrates that effective language learning is deeply influenced by both cognitive and affective factors. Traits such as perseverance, empathy, self-discipline, and emotional resilience are shown to facilitate communication and comprehension, suggesting a strong interdependence between character growth and linguistic development. The study concludes that The Miracle Worker is a powerful educational tool that can enhance students’ understanding of language acquisition concepts while also promoting reflective discussion on inclusive, empathetic teaching practices. By integrating academic content with character values, the film exemplifies a holistic approach to language education that addresses both intellectual and personal dimensions of learning. Keywords: The Miracle Worker, language acquisition, character education, content analysis, holistic education